The role of knowledge exchange in energy demand policy innovation - Downing, C; Higginson, S; Wilkins, T; Kobusinge, R; Simon, H; Jenkinson, K (European Council for an Energy Efficient Economy, 2021)
The purpose of this paper is to draw together lessons from a systematic review of academic knowledge exchange (KE) literature with the aim of informing the energy demand field, especially with regards to policy development. The exchange of knowledge between researchers and stakeholders such as policymakers is an essential part of ensuring that energy demand policy is evidence-based. At its most engaged, two-way KE involves researchers and policymakers both participating in, and sometimes even co-creating policy, in a long-term relationship. KE (and the tools, processes, skills, engagement methods and knowledge involved) is therefore critical to maximising the impact of research. This paper is based on a systematic review of the KE literature across eight thematic areas, taking ten papers from each area, resulting in a review of 80 papers. Analysis of these papers synthesised the factors necessary for effective KE. CREDS https://www.creds.ac.uk/ (Centre for Research into Energy Demand Solutions), is a major UK-based energy demand research programme, that is presented as a case study demonstrating the use of KE, in particular in relation to policy impact and innovation. The paper ends with combined lessons from the literature and the empirical evidence from CREDS.